Analysis of Marketing Development Strategies to Increase the Competitiveness of Sakinah Frozen Food Business in Paiton Probolinggo - Widad, Romzatul; Inayah, Fivia Saddha; Maharani, Resty Dwi; Maryam, Siti; Pramesti, Nabila Intan; Akhiriyah, Syahriatul (Journal of Economics and Social Sciences (JESS), 2025)
The development of the frozen food industry in Indonesia is growing rapidly in line with changes in people's lifestyles that prioritize practicality and efficiency. This sector is a potential opportunity for Micro, Small, and Medium Enterprises (MSMEs), including Sakinah Frozen Food which sells various frozen processed foods. However, competition with large manufacturers' products as well as limitations in digital promotion and marketing strategies are the main challenges faced. This research aims to analyze marketing development strategies that can increase the competitiveness of Sakinah Frozen Food in the digital era. The approach used is a qualitative descriptive method with data collection techniques in the form of observation, in-depth interviews with business owners, and documentation of marketing activities carried out. Data analysis was carried out using the 7P marketing mix theory and Porter's competitiveness concept, to identify strengths, weaknesses, opportunities, and threats (SWOT analysis) in the marketing strategy of the business. This study discusses aspects of marketing promotional capacity through social media. The results show that Sakinah Frozen Food has strength in terms of product completeness, competitive prices, and responsive service to local consumers. However, there are still weaknesses in terms of digital promotion and the use of online platforms such as marketplaces and application-based delivery services